2015
DOI: 10.2147/ov.s66045
|View full text |Cite
|
Sign up to set email alerts
|

Targeting tumor vasculature through oncolytic virotherapy: recent advances

Abstract: The oncolytic virotherapy field has made significant advances in the last decade, with a rapidly increasing number of early- and late-stage clinical trials, some of them showing safety and promising therapeutic efficacy. Targeting tumor vasculature by oncolytic viruses (OVs) is an attractive strategy that offers several advantages over nontargeted viruses, including improved tumor viral entry, direct antivascular effects, and enhanced antitumor efficacy. Current understanding of the biological mechanisms of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 121 publications
(104 reference statements)
1
11
0
Order By: Relevance
“…However, tumor cells adjacent to tumor vasculature, appeared to have cleared the virus infection to allow for regrowth of GFP-negative and RFP-positive tumor cells (indicated by the yellow dotted line). Consistent with previous reports [17], we observed some infected cells lining perfused blood vessels on day one post-infection. Contrary to the suggestion that this reflects direct oncolytic destruction of tumor vasculature, we observed that by day six post-infection these cells became GFP negative, but remained viable and supported vessel perfusion, indicating the ability of infected cells lining vasculature to clear virus in vivo ( Figure 1A,B).…”
Section: Co-culture Ohsv-infected Tumor Cells With Endothelial Cells supporting
confidence: 93%
See 1 more Smart Citation
“…However, tumor cells adjacent to tumor vasculature, appeared to have cleared the virus infection to allow for regrowth of GFP-negative and RFP-positive tumor cells (indicated by the yellow dotted line). Consistent with previous reports [17], we observed some infected cells lining perfused blood vessels on day one post-infection. Contrary to the suggestion that this reflects direct oncolytic destruction of tumor vasculature, we observed that by day six post-infection these cells became GFP negative, but remained viable and supported vessel perfusion, indicating the ability of infected cells lining vasculature to clear virus in vivo ( Figure 1A,B).…”
Section: Co-culture Ohsv-infected Tumor Cells With Endothelial Cells supporting
confidence: 93%
“…Various oncolytic viruses (OVs) including oHSV can infect and lyse proliferating tumor cells and endothelial cells, resulting in reduced perfusion and anti-angiogenic effects [17,26,27]. However, we and others have uncovered that OV treatment induces secretion of VEGF and IL-8 in the tumor microenvironment (TME), thereby increasing angiogenesis in residual tumors after virus clearance [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…While it has been previously shown that tumor-stromal cross-talk modulates the sensitivity of cancer cells to oncolytic virues [49], ours is the first report, to our knowledge, to investigate the direct effect(s) of a stromal selective oncolytic viral vector on in vivo tumor progression. The current study differs from previous publications in that other reports have investigated the additional direct or indirect effects of targeted or armed oncolytic viruses (which primarily infect cancer cells) on other stromal components, especially the tumor vasculature [50]. …”
Section: Discussionmentioning
confidence: 85%
“…Multiple approaches exist to target the tumor vasculature using genetically engineered OVs [86]. These approaches could be divided into OVs targeting the tumor vasculature by infecting the tumor VECs or inhibiting (pathways of) angiogenic cytokines and proteins specifically.…”
Section: Engineered Oncolytic Viruses Targeting the Tumor Vasculaturementioning
confidence: 99%